An OGCM study of the impact of rain and river water forcing on the Bay of Bengal. Issue 4 (9th April 2016) - Behara, Ambica; Vinayachandran, P. N.
Abstract: Individual and combined effects of rainfall and river discharge on the Bay of Bengal (BoB) is investigated using an Ocean General Circulation Model. A set of four sensitivity experiments, forced with same air‐sea heat flux, but retaining either river runoff or rainfall or both is carried out. These experiments show that the river water is exported out of the bay along the western boundary during winter and rain water along the eastern boundary during summer. Runoff leads to a large (>3 psu) decrease in salinity in the northern bay during summer and along the western boundary during winter, with a weaker contribution from rainfall. The sea surface temperature response to freshwater forcing shows large spatial variations with eastern bay showing higher differences. The northwestern bay warms by ∼1.5°C in the presence of freshwater during summer, due to greater heat absorption within a shallow mixed layer (ML). This warming is caused in nearly equal proportions by rain and river water in early summer, but the contribution by river water dominates during peak and withdrawal phases of the summer monsoon. Northeastern bay, in contrast, is cooler by 1.5–3°C in the presence of freshwater, caused primarily by river runoff, owing to the winter cooling over a thin ML. Temperature inversions form due to surface cooling of a river stratified layer during winter in the northwestern bay and due to radiation penetrating below the ML during summer in the northeastern bay. Key Points: Model study of individual and combined impact of river and rain on stratification and circulation Model study of individual and combined impact of river and rain on stratification and circulation Contrasting response of SST in the western and eastern Bay of Bengal explained